(untitled) (Fiep Bulletin - online, 2014)
Currently, all sports games, particularly soccer, have recorded a very significant progress. It is also the result of thoughtful preparation and selection of talented players. This applies not only to senior soccer, but especially to junior soccer. There are very close relationships between elite senior soccer and elite junior soccer. The authors of this project draw on the experience based on present knowledge of theory and practice of sports training of talented soccer players and want to submit a proposal for an improvement of talent identification and selection of young soccer players for the different age categories of youth national teams. Authors in theirs multiannual research (currently 2nd year of research) pursuing a level of functional parameters of the selected youth soccer players of Slovak Republic in teams U16 to U19. They compare obtained results for each player (their dynamics of change s) in each team U16 to U19, and also within different player positions. Acknowledgement: This study is a part of VE GA research grant No. 1/1252/12: “Improvement of identification and selection system of young male talented soccer players for junior national teams in the Slovak Republic and streamlining the content of their training and preparation.”